The battle over rights in Switzerland: populist arguments against international law - D'Amato, Gianni (Lund: Nordic Academic Press, 2019)
If there is a genuine conflict of laws between federal and inter national law, Switzerland’s obligation under international law takes precedence; this applies even to agreements that do not concern human rights or fundamental freedoms. The precedence set out above also applies in relation to subsequent federal laws, i.e. those which have entered into force in accordance with international law; the lex posterior rule does not apply in the relationship between international law and national law. Switzerland cannot invoke its domestic law to justify the non-fulfilment of a treaty. Accordingly, federal legislation contrary to international law remains regularly inapplicable. (Federal Court Ruling BGE (2012) 139 I 16, p. 28)